The Influence of Hydrogeology to Generation of Hydrogen Sulfide of Low-Rank Coal in the Southeast Margin of Junggar Basin, China - Qigen Deng; Tao Zhang; Fajun Zhao; Hao Wang; Jingping Yin (Geofluids)
The salinity, chemical properties, and migration characteristics of groundwater in coal measures are the key factors that affect the generation, migration, and reservoir of hydrogen sulfide (H2S) in low-rank coal seams. Taking the Jurassic coal and rock strata in the southeastern margin of the Junggar basin as the research object, according to the hydrogeological characteristics of the coal measures, the region is divided into 4 hydrogeological units. The coalbed methane contains a large number of secondary biogas. Along the direction of groundwater runoff, the salinity and the pH value increase gradually. The salinity in the hydrogeological units is low; it is not conducive to the propagation of sulfate-reducing bacteria and the formation of hydrogen sulfide of the Houxia, the south of Manasi River, and Hutubi and Liuhuangou area, the western region of the Miquan. The high salinity center and depressions of low water level (hydrodynamic stagnation zone) in the hydrogeological unit of the Liuhuanggou and the Miquan are the main areas for the production and enrichment of H2S in the low-rank coal. The high salinity in water is formed by infiltration, runoff, and drought evaporation. At the same time, the deep confined water environment closed well; in conditions of hydrocarbon-rich, under the action of sulfate-reducing bacteria, bacterial sulfate reduction will occur and hydrogen sulfide formed. According to the circulation characteristics of water bearing H2S in the region, imbricate and single bevel two kind generation and enrichment mode of hydrogen sulfide under the action of hydrodynamic control. The solubility of hydrogen sulfide in pure water and solutions of NaCl and Na2SO4 with different molar concentrations was calculated. The H2S solubility of groundwater in coal measures of 4 hydrogeological units was estimated.